CMOS Compatible Transient Resistive Memory with Prolonged Lifetime. Issue 9 (11th June 2019) - Zhong, Shuai; Ji, Xinglong; Zhou, Yinning; Zhang, Yishu; Ye, Ai; Zhao, Rong
Abstract: Transient resistive memory has attracted widespread attention because of its potential applications in disposable electronics and bioelectronics. Although various memory structures have been reported with good transient behaviors, their incompatibility with the complementary metal–oxide–semiconductor (CMOS) process has limited large‐scale integration to form transient electronic systems. In addition, the use of highly fluid‐sensitive materials results in memory with a short lifetime in minutes, which is far from being practical. Here, a transient resistive memory is demonstrated with W/Cu/SiO2 /W structure that is fully CMOS compatible and has a stable memory performance with high uniformity and excellent transient behaviors in water and biofluids. Furthermore, the dissolution test shows that W is a better electrode choice for prolonging the lifetime of transient memory. Together with a 30 nm Al2 O3 encapsulation layer, the device achieves a lifetime of approximately three months at room temperature, which is about four orders of magnitude loner than the best reported transient resistive memories at present. In addition, biocompatibility investigation shows that dissolved memory is not toxic to cell growth and viability, indicating good biocompatibility. This work enables the large‐scale integration of transient resistive memory with other transient components for practical applications. Abstract : A complementary metal–oxide–semiconductor compatible transient resistive memory with good uniformity, fully dissolution performance, and excellent biocompatibility is demonstrated. With facile ultrathin encapsulation, its lifetime can reach up to 3 months which is four orders higher than previous studies. This work paves the way for large scale production and long‐term application.